Growth of weeds in cereal populations - Erviö, Leila-Riitta (Agricultural and Food Science, 1972)
The weeds in this study consisted mainly of Chenopodium album, Stellaria media, Viola arvensis, Polygonum convolvulus, P. aviculare and P. lapathifolium. Increasing cereal seed rates reduced the numbers, individual weights and total yields of the most abundant species, Chenopodium album. The decreases in plant weight and total yield of the weeds were very steep when the cereal seed rate was raised from 25 to 200 kg/ha. Increases in the seeding rate reduced the total yields of weeds rather than their numbers. The effect of the cereal on weeds became apparent as soon as heading of the cereal was complete and was further enhanced by prolonged competition. Added nitrogen raised the weed yields at cereal seed rates of 25—100 kg/ha but reduced them at higher seed rates. Nitrogen also raised the yield and individual plant weight of C. album. Cereal seed rate did not affect the nitrogen, phosphorus, potassium, calcium and magnesium contents of the weeds grown among the crop. Due to larger total weed yields, however, the amounts of these nutrients in the weeds were higher in sparse than in dense cereal populations.